(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
In modern conditions of the global market, with the peculiarities of globalization and increased competition, manufacturing enterprises should strive not only to meet the needs of their domestic market, but also to develop large international markets through exports. Achieving a competitive advantage in the international arena requires the development and implementation of an effective operational strategy in the production of export-oriented products.